1933
DOI: 10.1172/jci100509
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Diabetic Acidosis

Abstract: Since the discovery that ketone acids are produced in the body and accumulate in the blood to excess in severe diabetes, general opinion has held that the accumulation of these chemical compounds is responsible for the syndrome known as diabetic coma. The general application of the term acidosis to the condition is in itself sufficient evidence of the importance which is attached to this disorder of metabolism. Difference of opinion seems to have been restricted chiefly to the question of the relative parts pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1933
1933
1955
1955

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 8 publications
(5 reference statements)
2
13
0
Order By: Relevance
“…There is no means of deciding how much of the deficit in any particular patient should be assigned to losses of body fluid alone, and how much is to be considered secondary to a disappearance of circulating plasma proteins of the type observed during depletion of body water and solutes (22,23 (24). In view of the dehydration described above, it is immediately apparent that these patients had lost, in keeping with the findings in other series, considerable amounts of the chief extracellular electrolytes, concomitant with, and in most instances, in excess of, the losses of body water (25,26). Had water alone been lost, the levels of sodium and chloride would have been increased above normal.…”
Section: Methods Of Calculationmentioning
confidence: 60%
See 1 more Smart Citation
“…There is no means of deciding how much of the deficit in any particular patient should be assigned to losses of body fluid alone, and how much is to be considered secondary to a disappearance of circulating plasma proteins of the type observed during depletion of body water and solutes (22,23 (24). In view of the dehydration described above, it is immediately apparent that these patients had lost, in keeping with the findings in other series, considerable amounts of the chief extracellular electrolytes, concomitant with, and in most instances, in excess of, the losses of body water (25,26). Had water alone been lost, the levels of sodium and chloride would have been increased above normal.…”
Section: Methods Of Calculationmentioning
confidence: 60%
“…The losses of body water, of extracellular electrolytes, of cell nitrogen, and of carbohydrate have been recognized and defined (25,26). The striking retention of potassium administered to this series of patients points to the existence of concomitant deficits of this cation in the body cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, other investigators have noted the factor of sex in ketosis, and hence further study is indicated. Peters (29) noted that female humans are more susceptible to ketosis, and Deuel and Hallman (30) observed a greater ketonemia following a high fat diet in fasted female rats than in pair-fed males. Friedemann (31) on the other hand noted that male monkeys fed a high fat diet excreted more ketones than females.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that the salt depletion which is so characteristic a feature of severe diabetic acidosis and coma (1) which had developed after voluntary omission of her usual insulin dosage, during a period in which her dietary intake had been markedly reduced. The difference in behavior may have been due to an inhibition of ketosis by the liberal carbohydrate administration during the 4-day experimental period as well as during the earlier study period.…”
Section: Plan Of Studymentioning
confidence: 82%
“…(Received for publication November 29, 1945) Diabetic patients with acidosis and coma commonly are markedly depleted of extracellular salt (1). This is often due, in part at least, to the persistent vomiting which frequently accompanies diabetic acidosis.…”
mentioning
confidence: 99%